Auditoría de cumplimiento y su relación con el front operativo del Banco Pichincha, sucursal Buena Fe, año 2013 - Ibarra Flores, Mayra Esthefany (2015)
The research proposal was carried out on the premises of the Bank located in the canton good faith, in the Avenida 7 of August and Vicente Rocafuerte esquina; and was directed to the Operational Front of Banco Pichincha, agency good faith had the following objectives: to determine the incidence of the audit of compliance in the above area; assess the level of compliance with laws and regulations, examine the procedures applied in the development of the activities implemented in the entity, assess internal control and formulate a report with the results of the compliance audit on the Operating Front of the entity. In the methodology we used methods: such as deductive and analyses- synthesis that facilitated the implementation of phases of the audit; the type of research also attended the field work, document review and description of findings. The assumptions made are accepted because they facilitated the revision of the legal framework to estimate the compliance activities and regulation guidelines; They also determined weaknesses that presents the Operating Front of Banco Pichincha, branch good faith. Outcomes include poor assessment to the staff of the Operating Front, reason for which corrective action is not taken and decisions favouring the performance of the entity; the evaluation of internal control was carried out with substantive evidence and documents showed the operating performance of the boxes and supervision area and provided a comparative analysis of the activities introduced in the manual of procedure, registering a high control risk. Ending with the issuance of the compliance audit report highlighting the failure to comply with applicable regulatory aspects in the entity; that will affect the operation of the Front Operating procedures.